(untitled) (Journal of Comparative Social Work, 2012)
The debate on classification instruments for social security regimes opened by Esping-Andersen (1990) usually neglects the examination of the normative impact of the welfare state. This article focus on this latter through an analysis of systems of protection against unemployment in 11 of the European countries included in the database known as the Mutual Information System on Social Protection (MISSOC).We show in this article that unemployment insurance only recognize legal, authorized and declared salaried employees who have resided in the country for a set period of time, which confirms the close link between social policy and nationality, with some foreign workers being excluded from the circle of beneficiaries because of these norms. Unemployment insurance also always considers jobs as rare social goods - workers are expected to hold on to them, but they are declined differently along a person’s life course. The dominance of the male employment norm and the complete lack of consideration given to domestic labour by unemployment insurance contribute to structuring gendered roles as separate and hierarchically organized. Disparities between countries, whether related to contextual differences or to the history of the local welfare state, do not weaken these arguments since they are not founded upon fundamentally different conceptions of unemployment.